Efek Perubahan Lingkungan Bisnis pada Profesi Akuntan Manajement - Sibilang, Novie (JBE (Journal of Business and Economics); Volume 8 No.1, 2009 JBE UNKLAB, 2009)
This Article Discuesses how Changes in the business environment have impacted on the management accounting Profession and how the profession responds to these “Challages”. Globalozation, the Rapid change of information technology, and business scandals that implicated accounting professiaon are there major factors that impact business activities. Now a days, business corporations have changed the way they operate in response to these changes in the environment. Management accounting, which provides the financial information of an organization that is affected by these changes. Globalization has increased the complexity of accounting records for multi Currency transactions; Increased the risk related to the application of business regulations and tax laws; and also opened up the jop market to the foreign accountants. Information technology has become a rival for the management accounting in providing the financial information for the business and accounting Propession. Professinalism is the answer to these ‘challenges’ for management accounting. The criterion for professinalism includes compotency and professional conduct. Competency for management accounting is how the profession prepares the financial information according to established criteria in an afficient manner, and analysez and communicates it to the user or public. Whereas, professional conduct relates to how the profession conducts itself according to the standards of conduct for management accounting. Competency is needed to respond to the globalization and information technology challenges, while professional conduct is needed to prevent future scandals in the profession.